Chatgpt adoption in university education: a dual perspective of healthcare educators and students - Sii, Elysha (2023)
Background: ChatGPT is an emerging transformative technology that carries significant societal implications. In order to gauge the level of understanding and preparedness of UTAR educators and students for this innovative tool, it is essential to assess their awareness of ChatGPT. By examining the understanding, perceptions, and attitudes of both educators and students towards such technologies, valuable insights can be gained, especially considering ChatGPT’s potential to play a crucial role in education. This study aims to explore and compare the awareness, perceptions, and opinions of educators and students concerning ChatGPT. Understanding the difference between these two groups can provide understanding into how technology is seen in the educational setting and how it might be successfully incorporated into the university learning environments at UTAR.